Comparative Effectiveness of Cognitive Behavioral Group Therapy and Emotion-Focused Therapy on Sexual Dysfunction in Patients with Cervical Cancer - Norouzi , Elham; Sobhani , Ahmad; Nikyar , Hamid Reza; Rezaie Jamalouei , Hasan (Psychology of Woman Journal, 2025)
Objective: The aim of this study was to compare the effectiveness of cognitive behavioral therapy (CBT) and emotion-focused therapy (EFT) on improving sexual function and its components in women diagnosed with cervical cancer.Methods and Materials: This quasi-experimental study utilized a pretest-posttest control group design with follow-up. Sixty women with cervical cancer referred to Vali-e-Asr Hospital in Zanjan were selected through purposive sampling and randomly assigned to two intervention groups (CBT and EFT) and one control group, with 20 participants in each. Both interventions were delivered in ten weekly group sessions. Data were collected using the Female Sexual Function Index (FSFI), which assesses six dimensions: sexual desire, arousal, lubrication, orgasm, satisfaction, and pain. Mixed-design ANOVA was used to analyze the effects of time, group, and their interaction, and Bonferroni post hoc tests were conducted for pairwise comparisons.Findings: Results indicated that both CBT and EFT significantly improved all components of sexual function and total FSFI scores compared to the control group (p < .001). Significant main effects of time, group, and interaction effects were observed for all variables. Bonferroni tests showed that both intervention groups had significantly higher posttest and follow-up scores in desire, orgasm, satisfaction, pain, and total FSFI compared to controls. However, no statistically significant differences were found between the CBT and EFT groups across most components (p > .05), and improvements were maintained at follow-up, indicating stability of treatment effects.Conclusion: These findings support the integration of psychotherapeutic interventions into comprehensive cancer care to enhance quality of life and relational well-being.